<span>Given: Right △ABC as shown where CD is an altitude of the triangle. We prove that
![a^2 + b^2 = c^2](https://tex.z-dn.net/?f=a%5E2%20%2B%20b%5E2%20%3D%20c%5E2)
Because △ABC and △CBD both have a right angle, and the same angle B is
in both triangles, the triangles must be similar by AA.
Likewise, △ABC
and △ACD both have a right angle, and the same angle A is in both
triangles, so they also must be similar by AA.
The proportions
![\frac{c}{a}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bc%7D%7Ba%7D%20)
and
![\frac{a}{f}](https://tex.z-dn.net/?f=%20%5Cfrac%7Ba%7D%7Bf%7D%20)
are
true because they are ratios of corresponding parts of similar
triangles.
The two proportions can be rewritten as
![a^2 = cf](https://tex.z-dn.net/?f=a%5E2%20%3D%20cf)
and
![b^2 = ce](https://tex.z-dn.net/?f=b%5E2%20%3D%20ce)
.
Adding
![b^2](https://tex.z-dn.net/?f=b%5E2)
to both sides of first equation,
![a^2 = cf](https://tex.z-dn.net/?f=%20a%5E2%20%3D%20cf)
, results in the
equation
![a^2 + b^2 = cf + b^2](https://tex.z-dn.net/?f=a%5E2%20%2B%20b%5E2%20%3D%20cf%20%2B%20b%5E2)
.
Because
![b^2](https://tex.z-dn.net/?f=b%5E2)
and ce are equal, ce can be
substituted into the right side of the equation for
![b^2](https://tex.z-dn.net/?f=b%5E2)
, resulting in the
equation
![a^2 + b^2 = cf + ce](https://tex.z-dn.net/?f=a%5E2%20%2B%20b%5E2%20%3D%20cf%20%2B%20ce)
.
Applying the converse of the distributive
property results in the equation
![a^2 + b^2 = c(f + e)](https://tex.z-dn.net/?f=a%5E2%20%2B%20b%5E2%20%3D%20c%28f%20%2B%20e%29)
.
The last sentence of the proof is
Because f + e = c,
![a^2 + b^2 = c^2](https://tex.z-dn.net/?f=a%5E2%20%2B%20b%5E2%20%3D%20c%5E2)
.</span>